1994
DOI: 10.1111/j.1540-8159.1994.tb03788.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effectiveness of In‐Office and Transtelephonic Follow‐Up in Terms of Pacemaker System Complications

Abstract: A study was undertaken to determine the most effective method of pacemaker follow-up in terms of the total number of complications detected and yield per follow-up in single and dual chamber pacing systems. The analysis involved 9,786 patient records from 635 patients. The records were reviewed with respect to method of follow-up, number of chambers paced, and complications detected. Complications included: oversensing, undersensing, noncapture, pocket and diaphragmatic stimulation, pacemaker mediated tachycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the USA, transtelephonic systems for pacemaker assessments have been used widely, sending baseline and magnet electrocardiogram (ECG) readings to a central operational base from the patient's home through a transtelephonic transmitter 2–4 . These systems, however, have never been implemented in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, transtelephonic systems for pacemaker assessments have been used widely, sending baseline and magnet electrocardiogram (ECG) readings to a central operational base from the patient's home through a transtelephonic transmitter 2–4 . These systems, however, have never been implemented in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of reassurance, it is obviously important not to miss significant pacemaker dysfunction. Some studies have found that in‐office follow‐up of pacemaker patients detects more cases of pacemaker dysfunction than transtelephonic follow‐up 7,8 . In fact, the Canadian Working Group on Cardiac Pacing recommends direct patient follow‐up rather than transtelephonic monitoring but recognizes that the latter may be more practical in geographically isolated patients and in cases where frequent monitoring is required 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Others have indicated that device problems could be identified throughout the life of a device and may be missed by TTM and that the existing Medicare guidelines may be inadequate for follow-up (13). What has become increasingly clear is that TTM may be useful for detecting battery depletion (14), but is significantly less effective in detecting all complications when compared with in-office pacemaker follow-up (15). This led to the recommendations by the Canadian Working Group on Cardiac Pacing that direct patient follow-up rather than TTM was desirable (16).…”
Section: See Page 2012mentioning
confidence: 95%